A MORN1‐associated HAD phosphatase in the basal complex is essential for Toxoplasma gondii daughter budding. (9th March 2016) - Engelberg, Klemens; Ivey, F. Douglas; Lin, Angela; Kono, Maya; Lorestani, Alexander; Faugno‐Fusci, Dave; Gilberger, Tim‐Wolf; White, Michael; Gubbels, Marc‐Jan
Summary: Apicomplexan parasites replicate by several budding mechanisms with two well‐characterized examples being Toxoplasma endodyogeny and Plasmodium schizogony. Completion of budding requires the tapering of the nascent daughter buds toward the basal end, driven by contraction of the basal complex. This contraction is not executed by any of the known cell division associated contractile mechanisms and in order to reveal new components of the unusual basal complex we performed a yeast two‐hybrid screen with its major scaffolding protein, Tg MORN1. Here we report on a conserved protein with a haloacid dehalogenase (HAD) phosphatase domain, hereafter named HAD2a, identified by yeast two‐hybrid. HAD2a has demonstrated enzyme‐activity in vitro, localizes to the nascent daughter buds, and co‐localizes with MORN1 to the basal complex during its contraction. Conditional knockout of HAD2a in Toxoplasma interferes with basal complex assembly, which leads to incomplete cytokinesis and conjoined daughters that ultimately results in disrupted proliferation. In Plasmodium, we further confirmed localization of the HAD2a ortholog to the basal complex toward the end of schizogony. In conclusion, our work highlights an essential role for this HAD phosphatase across apicomplexan budding and suggests a regulatory mechanism of differential phosphorylation on the structure and/or contractile function of the basal complex.